2016
DOI: 10.1007/s11420-016-9491-y
|View full text |Cite|
|
Sign up to set email alerts
|

Normal Femorotibial Rotational Alignment and Implications for Total Knee Arthroplasty: An MRI Analysis

Abstract: Background: Rotational alignment of prosthetic components in total knee arthroplasty (TKA) is important to successful outcomes. Component malrotation is a known cause of revision and understanding normal rotational alignment may help recreate normal joint kinematics. To date, no large MRI study assessing femorotibial rotational alignment in nonarthritic knees has been undertaken. Questions/ Purposes: Is Insall's tibial axis a reliable rotational landmark against common femoral rotational axes in the nonarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In fact, the MTT technique could lead to excessive external rotation of the tibial component 2,26 . Our results show that MTT was externally rotated by 0.5° ± 4.4°, a similar result to the one obtained by Wernecke, that showed 1.4° ± 4.9° externally rotated 12 . Some studies have suggested that the alignment of the tibial component with the center of PTM could be beneficial for patellofemoral tracking and anterior knee pain 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, the MTT technique could lead to excessive external rotation of the tibial component 2,26 . Our results show that MTT was externally rotated by 0.5° ± 4.4°, a similar result to the one obtained by Wernecke, that showed 1.4° ± 4.9° externally rotated 12 . Some studies have suggested that the alignment of the tibial component with the center of PTM could be beneficial for patellofemoral tracking and anterior knee pain 22 .…”
Section: Discussionsupporting
confidence: 92%
“…However, there have been considerable arguments regarding which rotational reference should be the standard for tibial alignment 10 . Traditionally, the anteroposterior (AP) axis is determined on tibial component during preoperative planning using various bony landmarks as references 11,12 . There are still arguments regarding whether the AP axis has the best reliability with the least variability, and also regarding the identification of the optimal AP axis of the tibial component 13 .…”
mentioning
confidence: 99%
“…In the 1990s, Insall [16] described an anteroposterior (AP) axis from the junction of the medial and the middle-thirds of the tibial tubercle to the PCL. Wernecke et al [20] performed MRI of 544 cases of normal knee joint and believed that Insall's axis was a reliable landmark for rotational alignment of the tibial component, which may optimize femorotibial kinematics in fixed-bearing TKA. Until date, the Insall's rotational axis for the tibial component in TKA has been generally accepted.…”
Section: Discussionmentioning
confidence: 99%
“…axis from the junction of the medial and the middle-thirds of the tibial tubercle to the PCL. Wernecke et al [20] performed MRI of 544 cases of normal knee joint and believed that Insall's axis was a reliable landmark for rotational alignment of the tibial component, which may optimize femorotibial kinematics in fixed-bearing TKA. Until date, the Insall's rotational axis for the tibial component in TKA has been generally accepted.…”
Section: Discussionmentioning
confidence: 99%